2008
DOI: 10.1016/j.jpain.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Subcutaneous Naloxone on Experimentally Induced Pain

Abstract: Telephone+61 8 9360 2415Fax +61 8 9360 6492Keywords: opioids; thermal hyperalgesia; peripheral opioid analgesia; cold pressor; pain tolerance; pain sensitivityRunning head: opioid analgesia and hyperalgesia -2 - ABSTRACTThe heat pain threshold was assessed in 32 healthy participants after a mild burn on the dorsal surface of each hand, after injection of an opioid antagonist (80 µg naloxone) or vehicle alone (0.2 mL saline) into the burnt skin of one hand, and after repeated painful immersion of this hand in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 41 publications
(38 reference statements)
0
26
0
Order By: Relevance
“…The demonstrated activation of spinal Dyn-ergic neurons by disinhibition suggests that they function as a high-gain antinociceptive system that is kept in reserve. Given numerous reports of the inability of opioid receptor blockade to lower nociceptive response thresholds and induce nociception (El-Sobky et al, 1976;Grevert and Goldstein, 1978;Robertson et al, 2008;Younger et al, 2009), it is widely accepted that endogenous opioid-ergic neurons are normally quiescent. The current study provides an expanded understanding of basal opioid-ergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstrated activation of spinal Dyn-ergic neurons by disinhibition suggests that they function as a high-gain antinociceptive system that is kept in reserve. Given numerous reports of the inability of opioid receptor blockade to lower nociceptive response thresholds and induce nociception (El-Sobky et al, 1976;Grevert and Goldstein, 1978;Robertson et al, 2008;Younger et al, 2009), it is widely accepted that endogenous opioid-ergic neurons are normally quiescent. The current study provides an expanded understanding of basal opioid-ergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In human research, µ-opioid receptor blockade antagonized stress-induced analgesia evoked by noxious electric shocks [47,48], immersion of a limb in ice-water [28,40], the perception of failure on a difficult cognitive task [2,3,20], a combat video shown to Vietnam veterans with post-traumatic stress disorder [38], and a first-time parachute jump [27]. Effects of µ-opioid receptor blockade on experimental pain are more variable [16,23,40], possibly because of individual differences in sensitivity to or release of opioid peptides. For example, naloxone augments shock-induced pain and cortical evoked potentials in pain-tolerant people, but inhibits pain and cortical evoked potentials in pain-sensitive people [10].…”
Section: Stress-induced Analgesiamentioning
confidence: 99%
“…For example, naloxone augments shock-induced pain and cortical evoked potentials in pain-tolerant people, but inhibits pain and cortical evoked potentials in pain-sensitive people [10]. We recently reported that µ-opioid receptor blockade facilitated pain induced by repeated immersions of a hand in ice-water in pain-tolerant subjects, but had no effect on pain induced by the first, less stressful, immersion [40]. In the present study, naltrexone failed to augment pain induced by electric shocks or single ice-water immersions in the group as a whole.…”
Section: Stress-induced Analgesiamentioning
confidence: 99%
“…Itch stimuli evoke scratching or biting, whereas noxious stimuli evoke a withdrawal reflex, flinching, or licking (Kuraishi et al 1995(Kuraishi et al , 2008Nojima et al 2004). Opioids, which are commonly used for alleviation of pain, elicit itching (Hales 1980;Jeon et al 2005;Maxwell et al 2005;Slappendel et al 2000); conversely, the opioid receptor antagonist naloxone enhances pain but inhibits the itch sensation (Metze et al 1999;Robertson et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Histamine-sensitive polymodal C fibers are also responsive to mustard oil, which is known to activate TRPA1, and there is no significant difference in the discharge patterns caused by itching or burning stimuli (Handwerker et al 1991). A new subtype of C fibers that is insensitive to mechanical stimuli was reported to respond to itch stimuli (Schmelz et al 1997). However, these fibers also respond to algogens such as capsaicin or bradykinin (Schmelz et al 2003).…”
Section: Introductionmentioning
confidence: 99%